Robin Watkins' 6th Birthday Party - Watkins, Howard::::::::: (1988)
Robin Watkins and friends in Watkins Family 1924 Model T Ford; ? And Adam Watkins on running board; Mary Roelke and Pat Doolittle holding granddaughter Emily Roelke